Organelle Crosstalk Regulators Are Regulated in Diseases, Tumors, and Regulatory T Cells: Novel Classification of Organelle Crosstalk Regulators - Liu, Ming; Wu, Na; Xu, Keman; Saaoud, Fatma; Vasilopoulos, Eleni; Shao, Ying; Zhang, Ruijing; Wang, Jirong; Shen, Haitao; Yang, William Y.; Lu, Yifan; Sun, Yu; et al. (Frontiers in Cardiovascular Medicine, 2021)
To examine whether the expressions of 260 OCRGs in 16 functional groups are modulated in 23 diseases and 28 tumors, we performed an extensive -omics data mining analyses and made a set of significant findings: 1) the ratios of upregulated versus downregulated OCRGs are 1:2.8 in acute inflammations, 1:1 in metabolic diseases, 1:1.2 in autoimmune diseases, and 1:3.8 in organ failures; 2) Sepsis and trauma-upregulated OCRG groups such as vesicle, mitochondrial (MT) fission and mitophagy but not others, which are termed as the cell crisis-handling OCRGs. Similarly, sepsis, trauma plus organ failures-upregulated seven OCRG groups including vesicle, MT fission, mitophagy, sarcoplasmic reticulum-MT, MT fusion, autophagosome-lysosome fusion, autophagosome/endosome-lysosome fusion are classified as the cell failure-handling OCRGs; 3) Suppression of autophagosome-lysosome fusion in endothelial and epithelial cells is required for viral replications, which classify this decreased group as the viral replication-suppressed OCRGs; 4) pro-atherogenic DAMPs such as oxLDL, LPS, oxPAPC and IFNs totally upregulated 33 OCRGs in endothelial cells including vesicle, MT fission, mitophagy, MT fusion, ER-MT contact, ER-PM junction, autophagosome/endosome-lysosome fusion, sarcoplasmic reticulum-MT, autophagosome-endosome/lysosome fusion and ER-GC interaction as the ten endothelial cell-activation/inflammation-promoting OCRG groups; 5) The expression of OCRGs are upregulated more than downregulated in Treg from lymph nodes, spleen, peripheral blood, intestine, brown adipose tissue in comparison to that of CD4+CD25- T effector controls; 6) TLRs, ROS regulator Nrf2 and inflammasome activated regulator caspase 1 regulated the expressions of OCRGs in diseases, virus infected cells and pro-atherogenic DAMPs treated ECs; 7) OCRG expressions are significantly modulated in all the 28 cancer datasets; the up-regulated OCRGs are correlated with tumor immune infiltrates in some tumors; and 8) tumor promoter factor IKK2 and tumor suppressor Tp53 significantly modulate the expressions of OCRGs. Our findings provide novel insights on the roles of upregulated OCRGs in the pathogenesis of inflammatory diseases and cancers, novel pathways for the future therapeutic interventions for inflammations, sepsis, trauma, organ failures, autoimmune diseases, metabolic CVDs, and cancers.